2010
DOI: 10.1007/s00383-010-2662-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention for patent ductus venosus

Abstract: Patent ductus venosus (PDV) is a rare condition, which usually presents secondary to hepatic atrophy and hepatic failure. We have treated eight cases of PDV, all with hypergalactosemia and hyperbilirubinemia. Ultrasonography and three-dimensional computed tomography demonstrated communication between the portal vein and the inferior vena cava. Of the eight PDV cases, three from the older age group (ages 9, 11, and 14 years) had high-density lesions in their brain nucleus, and one case (age 19 years) had underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…However, it was confirmed that the visible intrahepatic portal venous system is actually also present in patients with PSS and surgical closure of PSS can be successfully done [16]. Surgical treatment options for PSS include ligation, banding, coiling and stenting [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it was confirmed that the visible intrahepatic portal venous system is actually also present in patients with PSS and surgical closure of PSS can be successfully done [16]. Surgical treatment options for PSS include ligation, banding, coiling and stenting [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Two studies use the results of neonatal screening for galactosemia after a few days of feeding to estimate the prevalence of congenital portosystemic shunts 144,145 : High concentrations of blood galactose, unexplained by an abnormal activity of the enzymes of galactose metabolism, can be found in neonates 11,16,24,25,27,29,38,41,44,51,53,55,59,64,68,70,76,84,94,96,101,105,106,[118][119][120][121]126 with CPSS because galactose from milk bypasses the liver. The overall prevalence is close to 1:30,000 births and the prevalence of permanent CPSS can be estimated at 1:50,000.…”
Section: Prevalence and Possible Mechanismsmentioning
confidence: 99%
“…In all other cases, closure of the shunt should be considered early, to prevent complications from occurring, for four reasons: (1) hepatopulmonary syndrome and pulmonary hypertension may be present during the very first years of life; (2) the regression of pulmonary hypertension cannot be ascertained once irreversible lesions of the pulmonary arteries are present; (3) chronic hyperammonemia and high blood levels of manganese have adverse effects on the developing brain 160,161 ; and (4) the plasticity of the intrahepatic portal system may be better in younger children. 121 The plasticity of the intrahepatic portal system will allow revascularization of the liver even when the intrahepatic portal system is not detectable on imaging studies and when portal pressure is high during an occlusion test. The experience gained over the past 15 years indicates that there is very little place left, if any, for liver transplantation in the management of congenital portosystemic shunts in children.…”
Section: Indications For Closurementioning
confidence: 99%
“…From several literature reviews and case reports, the disease appears to be more prevalent in the Japanese population. In total, there have been 173 human cases of EHPSS reported (Caruso et al 2010; Franchi-Abella et al 2010; Kobayashi et al 2010; Konstas et al 2010; Lautz et al 2011; Newman et al 2010; Ohno et al 2008) and 89 human cases of IHPSS (Ferrero et al 2010; Franchi-Abella et al 2010; Kamimatsuse et al 2010; Konstas et al 2010; Ohno et al 2008; Schierz et al 2011; Stringer 2008; Tsai et al 2009; Uchino et al 1999; Yoshimoto et al 2004). In human EHPSS, a classification has been made based on the presence or absence of portal blood flow (Abernethy 1793).…”
Section: Congenital Portosystemic Shunts In Man and Comparison With Dogsmentioning
confidence: 99%